Adaptive spatial-temporal resolution optical vehicular communication system using image sensor. (November 2017) - Islam, Amirul; Hossan, Md. Tanvir; Nguyen, Trang; Jang, Yeong Min
In this article, we introduce an image sensor–based optical vehicular communication system for performing vehicular condition resolution adaptively in the spatial domain and the temporal domain. To validate the proposed system, a dual camera–based approach is presented here, where a vision camera is used to detect multiple vehicles of interest (i.e. spatial condition), a communication link is set up, and then, a high-speed camera adapts its resolution to ensure fast processing and high-rate data communication (i.e. temporal condition). We suggest an adaptive algorithm that supports the detection of and communication multiple vehicles simultaneously in spatial-temporal condition. Moreover, we propose a combination of scale-invariant feature transform and iterative closest point for detection and classification of multiple vehicles. To prove the feasibility of our proposed scheme, we present simulation results.